Plato's Charmides and the Socratic ideal of rationality - Schmid, Walter T. (SUNY series in ancient Greek philosophy, 1998)
In this book, W. Thomas Schmid demonstrates that the Charmides - a platonic dialogue seldom referenced in contemporary studies - is a microcosm of Socratic philosophy. He explores the treatment of the Socratic dialectic, the relation between it and the Socratic notion of self-knowledge, the Socratic ideal of rationality and self-restraint, the norm of holistic and moral health, the interpretation of the soul as the rational self, the Socratic attitude toward democracy, and the connections between dialectic autonomy and moral community. Schmid argues that the depiction and account of sophrosune - human moderation - in the Charmides adumbrates Plato's vision of the life of critical reason, and of its uneasy relation to political life in the ancient city.